2018
DOI: 10.21608/mjcu.2018.55761
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Anemia and Microvascular Complications in Patients with Type 2 Diabetes Mellitus

Abstract: Background:Recently, it has been demonstrated that anemia may be an etiological factor in development of microvascular complication in type 2 D.M. patients.Objective: Evaluation of the relation between anemia and microvascular complications in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…The finding of this study showed that T2DM patients with anemia have an increased risk of developing diabetic microvascular complications, which might be due to tissue hypoxia and hemodynamic effects in diabetic tissues ( 36 ). Previous studies showed an association between anemia and microvascular complications in patients with T2DM ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 87%
“…The finding of this study showed that T2DM patients with anemia have an increased risk of developing diabetic microvascular complications, which might be due to tissue hypoxia and hemodynamic effects in diabetic tissues ( 36 ). Previous studies showed an association between anemia and microvascular complications in patients with T2DM ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 87%